Bifunctional catalyst and method and application thereof for improving selectivity and yield of catalytic production of propane from synthesis gas

By using a dual-function catalyst of CuCr2O4 and H-SSZ-13 molecular sieve with spinel structure, the structural parameters and abrasive particle size are adjusted, and the problems of uncontrollable carbon chain, many by-products and low yields in the propane production process in the prior art are solved, and the production of propane with high selectivity and high yield is achieved, and the catalyst life is significantly extended.

CN119549190BActive Publication Date: 2025-04-25MAPLE NEW MATERIAL TECH (SHANDONG) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510111918.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25
Estimated Expiration
2045-01-24

Smart Images

  • Figure CN119549190B_ABST
    Figure CN119549190B_ABST
Patent Text Reader

Abstract

The present invention provides a bifunctional catalyst and a method and application thereof for improving the selectivity and yield of catalytic preparation of propane from synthesis gas, belonging to the technical field of material catalysts. The bifunctional catalyst provided by the present invention includes CuCr2O4 and H‑SSZ‑13 molecular sieves of spinel structure, wherein CuCr2O4 has the stability of spinel structure, which can ensure that the catalyst maintains its structure and performance during long-term use, and the number of surface oxygen vacancies is abundant, which can play an efficient and stable catalytic role. At the same time, the 2θ of H‑SSZ‑13 molecular sieve and the corresponding relative peak area and the 2θ of H‑SSZ‑13 molecular sieve and the corresponding single crystal face grain size are set within the required range, which can be beneficial to control the life of the catalyst and to improve the selectivity of propane, so that the yield of propane can be improved by improving the conversion rate of synthesis gas and the high selectivity of propane in the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material catalysts, and in particular relates to a bifunctional catalyst and a method and application thereof for improving the selectivity and yield of catalytically preparing propane from synthesis gas. Background Art

[0002] Propane is an important alkane material and an important basic raw material for modern chemicals and liquefied petroleum gas. The market demand is increasing year by year. Propane can be produced through the Fischer-Tropsch synthesis route. The Fischer-Tropsch synthesis route using Fe, Co or Rh-based catalysts generally has a high CO2 conversion rate, but due to the limitations of the Anderson-SchultzFlory (ASF) rule, the carbon chain type of the target product is uncontrollable, there are many types of by-products, and the yield of the target product is low.

[0003] CN 1054202A discloses a catalyst for preparing propane from synthesis gas with high selectivity, which is a composite of Cu-Zn / Al2O3 (or Cu-Zn / Cr2O3) and HY molecular sieve, and has a carbon monoxide conversion rate of more than 64% and a propane selectivity of more than 96.2%. The carbon monoxide conversion rate in this method is slightly low, but this directly affects the yield of propane and also leads to a low yield. At the same time, the catalytic time for maintaining the propane selectivity is only 150 hours.

[0004] CN 103508828A mentions that a H2 / CO mixed gas with a molar ratio of 0.5 to 5.0 is catalyzed by a composite catalyst, resulting in an increase in carbon monoxide conversion rate to 75% and a total ethane / propane selectivity of 70%. Although this method has a high total selectivity for ethane / propane, the selectivity for a single component, propane, is uncontrollable. Summary of the invention

[0005] The present invention provides a bifunctional catalyst and a method and application thereof for improving the selectivity and yield of catalytic production of propane from synthesis gas. The bifunctional catalyst can be beneficial for controlling the life of the catalyst and improving the selectivity of propane, and can improve the yield of propane by increasing the conversion rate of synthesis gas and the high selectivity of propane in the product.

[0006] In order to achieve the above-mentioned object, the present invention provides a bifunctional catalyst, comprising CuCr2O4 with a spinel structure and H-SSZ-13 molecular sieve, wherein when the 2θ of the H-SSZ-13 molecular sieve is 9.59°, 13.01°, and 20.81°, respectively, its single crystal plane grain size corresponds to 60-65nm, 55-70nm, and 50-60nm, respectively.

[0007] It is understood that the CuCr2O4 used in the above scheme has the stability of the spinel structure, which can ensure that the catalyst maintains its structure and performance during long-term use, and the surface oxygen vacancies are abundant, which can play an efficient and stable catalytic role. It can also be understood that the 2θ of the H-SSZ-13 molecular sieve and the corresponding single crystal face grain size are set within the above range, respectively, to expose more pores, which will be beneficial to improve the selectivity of propane. When the average grain size is less than 50nm or 2θ is 9.59° less than 60nm or 2θ is 13.01° less than 55nm or 2θ is 20.81° less than 50nm, the stability of the molecular sieve framework is reduced, affecting the life of the catalyst; or when the average grain size is greater than 70nm, or 2θ is 9.59° greater than 65nm or 2θ is 13.01° greater than 70nm or 2θ is 20.81° greater than 60nm, the selectivity for propane is significantly reduced.

[0008] Preferably, the average crystal size of the H-SSZ-13 molecular sieve is 50 to 70 nm.

[0009] Preferably, when the 2θ of H-SSZ-13 molecular sieve is 9.59°, 13.01°, and 20.81°, the relative peak areas are 1, 0.30-0.40, and 0.70-0.90, respectively, wherein the relative peak area is the area relative to the peak area of ​​2θ=9.59°. It is understandable that by setting the 2θ of H-SSZ-13 molecular sieve and the corresponding relative peak area within the above range, the growth level of each crystal face can be effectively controlled to be relatively suitable, which is beneficial to controlling the life of the catalyst. When the relative peak area of ​​2θ is 13.01° and is lower than 0.30 or the relative peak area of ​​2θ is 20.81° and is lower than 0.70, the crystallinity of the material is poor and the stability of the catalyst structure is poor; or when the relative peak area of ​​2θ is 13.01° and is higher than 0.40 or the relative peak area of ​​2θ is 20.81° and is higher than 0.90, the selectivity of propane will be affected.

[0010] Preferably, the molar ratio of SiO2 / Al2O3 in the H-SSZ-13 molecular sieve structure is (10-20): 1. It can be understood that when the molar ratio of SiO2 / Al2O3 of H-SSZ-13 molecular sieve is (10-20): 1, it has abundant acid sites and high acid strength, and has high catalytic efficiency and conversion rate when catalyzing propane from synthesis gas; when the molar ratio of SiO2 / Al2O3 is greater than 20: 1, the acid sites are reduced and the carbon monoxide conversion rate is reduced; when the molar ratio of SiO2 / Al2O3 is less than 10: 1, the non-framework aluminum content increases, and the H-SSZ-13 molecular sieve structure is extremely unstable.

[0011] Preferably, the bifunctional catalyst is prepared by grinding and tableting spinel-structured CuCr2O4 and H-SSZ-13 molecular sieve, respectively, and then crushing them into particles of 20 to 40 meshes.

[0012] Preferably, the mass ratio of the spinel structured CuCr2O4 and the H-SSZ-13 molecular sieve is 1:1.

[0013] Preferably, the H-SSZ-13 molecular sieve is prepared by the following steps:

[0014] The sodium source, silicon source, aluminum source and organic template are dissolved in water and stirred to form a silica-alumina gel. The product is crystallized at 160-180°C for 7-10 days. The product is filtered and dried to obtain the raw powder of SSZ-13 zeolite molecular sieve. The raw powder is then ammonium exchanged and calcined to obtain H-SSZ-13 molecular sieve.

[0015] Preferably, the aluminum source is sodium aluminate, the sodium source is sodium hydroxide, the silicon source is sodium silicate Na2SiO3, and the organic template is (2-aminoethyl)trimethylammonium chloride hydrochloride.

[0016] Preferably, the sodium source is calculated as Na2O, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the organic template is calculated as (2-aminoethyl)trimethylammonium chloride hydrochloride, and the mass molar ratio of the added sodium source, silicon source, aluminum source, organic template and water is (0.15-0.45):1:(0.01-0.15):(0.2-3.0):(20-80).

[0017] Preferably, the ammonium exchange of the original powder is specifically carried out in the following steps:

[0018] The original powder was calcined at 500-600°C for 10-12h to remove the template, stirred and exchanged 2-3 times at 60-70°C in a water bath in a solution with an ammonium concentration of 3-5 mol / L, filtered, and then dried at 100-120°C. After that, it was placed in a muffle furnace and heated to 500°C at a rate of less than 5°C / min. After keeping the temperature for 2-3h, the H-SSZ-13 molecular sieve was obtained.

[0019] The present invention also provides an application of the bifunctional catalyst according to any one of the above technical solutions in improving the conversion rate of the synthesis gas catalytic process to enhance the high selectivity and high yield of propane.

[0020] Preferably, in the synthesis gas catalytic process based on the bifunctional catalyst, the conversion rate of carbon monoxide reaches 78%, and the selectivity and yield of propane are above 80% and 50% respectively.

[0021] Preferably, in the synthesis gas catalytic process based on the bifunctional catalyst, after 500 hours of continuous catalysis, the yield of propane still maintains more than 90% of the initial level.

[0022] The present invention also provides a method for improving the selectivity and yield of catalytic production of propane from synthesis gas, wherein the bifunctional catalyst described in any one of the above technical solutions is added to the catalytic process of synthesis gas.

[0023] Compared with the prior art, the advantages and positive effects of the present invention are:

[0024] The bifunctional catalyst provided by the present invention comprises CuCr2O4 and H-SSZ-13 molecular sieve of spinel structure, wherein CuCr2O4 has the stability of spinel structure, which can ensure that the catalyst maintains its structure and performance during long-term use, and at the same time, the number of surface oxygen vacancies is abundant, which can play an efficient and stable catalytic role. At the same time, the 2θ of H-SSZ-13 molecular sieve and the corresponding relative peak area and the 2θ of H-SSZ-13 molecular sieve and the corresponding single crystal face grain size are respectively set within the required range, which can be beneficial to control the life of the catalyst and to improve the selectivity of propane, so as to improve the yield of propane by improving the conversion rate of synthesis gas and the high selectivity of propane in the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The XRD spectrum of H-SSZ-13 prepared in the embodiment of the present invention is shown. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] Preparation of H-SSZ-13 molecular sieve

[0029] Dissolve a sodium source, a silicon source, an aluminum source, and an organic template in water, wherein the sodium source is calculated as Na2O, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the template is calculated as T, and the molar ratio of Na2O:SiO2:Al2O3:T:H2O in the raw materials is 0.15:1:0.05:3.0:20; stir to form a silica-alumina gel, and crystallize at 160°C for 8 days; filter and dry the product to obtain the raw powder of SSZ-13 zeolite molecular sieve.

[0030] The original powder was calcined at 500℃ for 10h to remove the template agent, and then stirred and exchanged three times in a water bath with an ammonium radical concentration of 3 mol / l at 70℃, filtered, and dried at 120℃. After that, it was placed in a muffle furnace and heated to 500℃ at 4℃ / min. After keeping the temperature for 3h, H-SSZ-13 molecular sieve was obtained. Its XRD spectrum is shown as follows: Figure 1 shown.

[0031] In the above preparation process, the aluminum source is sodium aluminate, the alkali source is sodium hydroxide, the silicon source is sodium silicate, the ammonium exchange reagent is ammonium nitrate, and the organic template is (2-aminoethyl) trimethylammonium chloride hydrochloride.

[0032] Analysis of the Crystal Structure of H-SSZ-13 Molecular Sieve

[0033] The test was carried out using a Bruker D8 Advance X-ray diffractometer with a scanning angle of 5° to 40°, a step length of 0.02° / step, and a scanning time of 0.12S / °. After obtaining the diffraction spectrum, the jade analysis software was used to perform relative peak area and single crystal plane size analysis for 2θ of 9.59°, 13.01°, and 20.81°, and the average grain size analysis was performed using the full spectrum fitting method of jade.

[0034] Combination Figure 1 Further analysis of the XRD spectrum shown shows that the average grain size of the H-SSZ-13 molecular sieve is controlled at (50-70) nm, and the key crystal surface indicators are shown in Table 1.

[0035] Table 1

[0036]

[0037] *: The relative peak area is the area relative to the peak area at 2θ=9.59° (±0.2°).

[0038] Examples 2-7 and Comparative Examples 1-10

[0039] The molecular sieves of Examples 2-7 and Comparative Examples 1-10 were prepared using the same H-SSZ-13 molecular sieve as in Example 1, except that the preparation parameters used, such as the molar ratio of the added raw materials, reaction conditions, etc., changed, as shown in Table 2 for details.

[0040] Table 2

[0041]

[0042] Preparation of bifunctional catalysts

[0043] The spinel structured CuCr2O4 and the H-SSZ-13 molecular sieves obtained in Examples 1-7 and Comparative Examples 1-10 were fully ground, mixed and pressed into tablets in a mass ratio of 1:1, and then crushed into 40 mesh particles.

[0044] Catalytic production of propane from syngas

[0045] The bifunctional catalyst particles obtained above were respectively loaded in a fixed bed reactor. After the catalyst was loaded (loading amount was 2 g), it was reduced at 280°C for 5 h in a hydrogen atmosphere with a hydrogen flow rate of 20 ml / min. After the reduction was completed, the reaction temperature was adjusted and the reducing gas was switched to the reaction gas with a H2 / CO molar ratio of 4. The reaction products were introduced into the gas chromatograph in gaseous form for online analysis.

[0046] The carbon monoxide conversion rate, propane selectivity and yield were calculated based on the changes in the content of each component. After the catalyst has been working continuously for a certain period of time, the time when the yield remains above 90% of the initial level is recorded as the life of the catalyst. The results are shown in Table 3.

[0047] Table 3

[0048]

[0049] Combined with Tables 2 and 3 above, it can be seen that the SiO2 / Al2O3 molar ratio of the raw material feed in Examples 1 to 3 and 4 to 5 is in the range of 1: (0.05 to 0.15), the silicon-aluminum molar ratio of the synthesized H-SSZ-13 molecular sieve is reduced, the catalyst surface acid sites are more, and the carbon monoxide conversion rate is above 78%; the sodium oxide and water content of the raw material feed affects the alkalinity of the synthesis system. The higher the alkalinity, the easier it is to dissolve the molecular sieve, which reduces the grain size and peak area. When Na2O is in the range of (0.15-0.45) and H2O is in the range of (20-80), the average grain size of the molecular sieve is controlled at (50-70) nm, and the crystal plane grain sizes of 2θ of 9.59°, 13.01°, and 20.81° are in the range of (60-65) nm, (55-70) nm, and (50-60) nm, respectively, and the relative peak areas of 2θ of 13.01° and 20.81° are greater than 0.3 and greater than 0.7, respectively, and the propane selectivity and lifetime are greater than 80% and greater than 500 h, respectively.

[0050] Examples 6-7: The amount of template used is 0.2-3.0, which can ensure that the material structure has high stability. The relative peak area of ​​the synthesized molecular sieve is 13.01°, which is greater than 0.30, and the relative peak area of ​​2θ is 20.81°, which is greater than 0.70. The catalyst life can reach more than 500 hours.

[0051] In Comparative Examples 1 to 4, when Na2O is lower than 0.15 or H2O is higher than 80, the basicity of the system decreases, the crystal plane grain sizes of 2θ are 9.59°, 13.01°, and 20.81°, and the average grain size increases, and the selectivity for propane decreases; when Na2O is higher than 0.45 or H2O is lower than 20, the basicity of the system increases, the relative peak areas of 2θ are 13.01° and 20.81° decrease, the stability of the molecular sieve framework decreases, and the catalyst life is shortened; and the crystal plane grain sizes of 2θ are 9.59°, 13.01°, and 20.81°, and the average grain size decreases, and the propane selectivity deteriorates.

[0052] In Comparative Examples 5-6, the SiO2 / Al2O3 molar ratio of the feed is higher than (1:0.05), resulting in the SiO2 / Al2O3 molar ratio of the molecular sieve being greater than 20, the acid sites of the catalyst are reduced, and the carbon monoxide conversion rate is reduced; the SiO2 / Al2O3 molar ratio of the feed is less than (1:0.15), resulting in the SiO2 / Al2O3 molar ratio of the molecular sieve being lower than 10, the molecular sieve framework is unstable, and the service life of the catalyst is greatly reduced.

[0053] In Comparative Examples 7-8, when the amount of template agent is greater than 3.0, the molecular sieve cannot be synthesized normally; when the amount of template agent is less than 0.15, the relative peak area of ​​2θ is 13.01° is less than 0.30 and the relative peak area of ​​2θ is 20.81° is less than 0.70 and the average grain size is less than 40nm and 2θ is 9.59° is less than 60nm and 2θ is 13.01° is less than 55nm and 2θ is 20.81° is less than 50nm, the carbon monoxide conversion rate, propane selectivity and catalyst life are all poor.

[0054] In Comparative Examples 9 to 10, after replacing with other templates, the grain size of the crystal plane with 2θ of 9.59° is greater than 65nm, the grain size of the crystal plane with 2θ of 13.01° is greater than 70nm, the grain size of the crystal plane with 2θ of 20.81° is greater than 60nm, and the average grain size is greater than 70nm, and the propane selectivity is reduced.

[0055] From the above analysis, it can be seen that by adjusting the key points of the bifunctional catalyst provided by the present invention within the set range, when applied to the process of catalytic preparation of propane from synthesis gas, a carbon monoxide conversion rate of 78% can be achieved, and the propane selectivity and yield are respectively above 80% and above 50%; and after the catalyst has worked continuously for 500 hours, the yield still maintains more than 90% of the initial level.

Claims

1. A bifunctional catalyst for improving the high selectivity and high yield of propane by improving the conversion rate of the synthesis gas catalytic process, characterized in that: The bifunctional catalyst comprises CuCr2O4 and H-SSZ-13 molecular sieve of spinel structure in a mass ratio of 1:1, wherein when the 2θ of the H-SSZ-13 molecular sieve is 9.59°, 13.01°, and 20.81°, the single crystal plane grain size thereof corresponds to 60-65nm, 55-70nm, and 50-60nm, respectively; Among them, the molar ratio of SiO2 / Al2O3 in the H-SSZ-13 molecular sieve structure is (10-20): 1; The H-SSZ-13 molecular sieve is prepared by the following steps: The sodium source, silicon source, aluminum source and organic template are dissolved in water, stirred to form a silica-alumina gel, and crystallized at 160-180°C for 7-10 days. The product is filtered and dried to obtain the raw powder of SSZ-13 zeolite molecular sieve, and then the raw powder is ammonium exchanged and calcined to obtain H-SSZ-13 molecular sieve; The aluminum source is sodium aluminate, the sodium source is sodium hydroxide, the silicon source is sodium silicate Na2SiO3, and the organic template is (2-aminoethyl)trimethylammonium chloride hydrochloride; the sodium source is calculated as Na2O, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the organic template is calculated as (2-aminoethyl)trimethylammonium chloride hydrochloride. The molar ratio of the added sodium source, silicon source, aluminum source, organic template and water is (0.15-0.45):1:(0.01-0.15):(0.2-3.0):(20-80).

2. The bifunctional catalyst according to claim 1, characterized in that The average crystal size of H-SSZ-13 molecular sieve is 50-70 nm.

3. The bifunctional catalyst according to claim 1, characterized in that When the 2θ of H-SSZ-13 molecular sieve is 9.59°, 13.01°, and 20.81°, respectively, the relative peak areas are 1, 0.30-0.40, and 0.70-0.90, respectively, wherein the relative peak area is the area relative to the peak area of ​​2θ=9.59°.

4. The bifunctional catalyst according to any one of claims 1 to 3, characterized in that The bifunctional catalyst is prepared by fully grinding CuCr2O4 with a spinel structure and H-SSZ-13 molecular sieve, mixing and tableting, and then crushing into particles of 20 to 40 meshes.

5. The bifunctional catalyst according to claim 1, characterized in that The ammonium exchange of the original powder is specifically carried out in the following steps: The original powder was calcined at 500-600°C for 10-12h to remove the template, stirred and exchanged 2-3 times at 60-70°C in a water bath in a solution with an ammonium concentration of 3-5 mol / L, filtered, and then dried at 100-120°C. After that, it was placed in a muffle furnace and heated to 500°C at a rate of less than 5°C / min. After keeping the temperature for 2-3h, the H-SSZ-13 molecular sieve was obtained.

6. Use of the bifunctional catalyst according to any one of claims 1 to 5 in improving the conversion rate of a synthesis gas catalytic process to increase the high selectivity and high yield of propane.

7. The use according to claim 6, characterized in that: In the synthesis gas catalytic process based on a bifunctional catalyst, the conversion rate of carbon monoxide reaches 78%, and the selectivity and yield of propane are above 80% and 50% respectively.

8. The use according to claim 6, characterized in that: In the synthesis gas catalytic process based on the bifunctional catalyst, after 500 hours of continuous catalysis, the yield of propane still maintained above 90% of the initial level.

9. A method for improving the selectivity and yield of catalytic synthesis of propane from synthesis gas, characterized in that: The bifunctional catalyst according to any one of claims 1 to 5 is added to the catalytic process of synthesis gas.

Citation Information

Patent Citations

  • Method used for preparing ethane and propane from synthetic gas

    CN103508828A

  • Propane catalyst prepared selectively from synthetic gas

    CN1054202A

  • Nano composite catalyst and preparation method and application thereof

    CN110743611A

  • Bifunctional catalyst as well as preparation method and application thereof

    CN112705259A